Features of the use of the statistical method of frequency stabilization of generators in distributed information-measuring systems - D. D. Gabrielyan; P. I. Kostenko; O. A. Safarian (Научный вестник МГТУ ГА)
The article deals with the problems of frequency stabilization of generators in distributed information-measuring systems on the basis of the static frequency stabilization method. The examples of similar systems are given. The necessity to ensure high stability of signal frequency generated by subscribers to improve the efficiency of the stated systems is noted. Two main features of applying the static frequency stabilization method are stated. The first one is determined with a delay in signal input into the device for estimating the frequency-time signal parameters in relation to the signal phase measurement interval. The second feature involves the entry delay of the formed control signal of generator frequency correction. It is shown that the mentioned features lead to divergence of the current variation of generator frequency and the value under correction, obtained considering the delay. The description of information signals enabling to specify a mathematical model of the process of assessment forming of the information signal frequency variation, taking into account the mentioned factors, is offered. It is shown that the possibility of using a statistical method to stabilize the frequency of generators in distributed informationmeasuring systems is determined not only with the values of nominal frequencies and relative instabilities of generators included into the information-measuring system, but also by the autocorrelation function of a random process describing the change of information signal frequency. In case of small time delays between the evaluation of information signal frequency and frequency stabilization, the use of the method to be considered allows to reduce the relative instability of information signal frequency. When time delays are greater than the correlation interval, the use of the statistical method does not lead to the change of relative instability of information signal frequency. Within the correlation interval, the use of the statistical method of frequency stabilization can cause depending on the autocorrelation function values both decrease and increase of the relative information signal frequency instability.